First report of maggots of family piophilidae recovered from human cadavers in Malaysia - Nazni, W.A.; Jeffery, J.; Sa'djyah, L.; Noorijuliana, W.M.; Chen, C.D.; Rohayu, S.A.; Hafizam, A.H.; Lee, H.L. (2008)
Piophila casei (Linnaeus) (Diptera: Piophilidae) is reported from human cadavers in two separate forensic cases for the first, time in Malaysia. Both bodies were found indoors. The first case, was that of a male of unknown nationality and age and also contained maggots of the muscid Ophyra spinigera (Stein). The second case was a female Chinese whose body also contained other species of maggots but these were not identifiable.